Comparison of In Vitro Antibacterial Activity of Epaltes divaricata and Vetiveria zizanioides against Methicillin-Resistant Staphylococcus aureus - Hasanga Rathnayake; Manikkuwadura Hasara Nethmini De Zoysa; Ruwani Punyakanthi Hewawasam; Weerasinghe Mudiyanselage Dilip Gaya Bandara Wijayaratne (Scientifica)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of hospital- and community-acquired infections worldwide. Therefore, this study was conducted to explore the antibacterial activity of the two medicinal plants Epaltes divaricata and Vetiveria zizanioides against strains of MRSA which were isolated from patients with skin and soft tissue infections. Hexane, ethanol, and water extracts of E. divaricata (whole plant) and V. zizanioides (roots) were prepared. Clinical isolates of MRSA strains (n = 20) were used for the study. Bacterial susceptibility was tested using a disc diffusion assay. Minimum inhibitory concentration (MIC) was determined by a broth microdilution method. Vancomycin was used as the positive control. Hexane, ethanol, and water extracts of E. divaricata showed inhibitory zones against MRSA. Except for water extract, both hexane and ethanol extracts of V. zizanioides showed inhibitory zones. MIC ranges of hexane, ethanol, and water extracts in E. divaricata were 0.012–0.32 mg/mL, 0.019–2.4 mg/mL, and 0.019–0.48 mg/mL, respectively. Respective MIC ranges of hexane and ethanol extracts of V. zizanioides were 0.003–0.032 mg/mL and 0.019–2.4 mg/mL. The hexane extract of V. zizanioides inhibited 55% of the selected MRSA strains at a relatively low MIC value of 0.012 mg/mL. The hexane extract of both plants demonstrated inhibition of 75% of MRSA strains at a MIC value of 0.064 mg/mL. Ethanol extract of V. zizanioides and E. divaricata, respectively, inhibited 70% and 45% of MRSA strains at the MIC of 0.096 mg/mL, whereas water extract of E. divaricata inhibited 80% of MRSA strains at the same MIC. Both E. divaricata and V. zizanioides were equally effective against MRSA at a MIC of 0.064 mg/mL. But V. zizanioides was more effective since the hexane extract inhibited more than 50% of MRSA strains at significantly a lower MIC value of 0.012 mg/mL. Fractionation, purification, and identification of active compounds will warrant further evaluation of the therapeutic potential of both plant extracts.